Strengthening The Role Of Indigenous Communities In Sustainable Natural Resource Governance - Nurhidayah, Andi; Rusdi , Andi Muhammad (Green Publisher Indonesia, 2025)
The role of indigenous peoples in natural resource governance (SDA) is a crucial aspect in realizing sustainable development, especially in areas that have been the living space of indigenous communities. Unfortunately, in practice, the contributions of indigenous peoples are often marginalized by the state's formal legal-formal approach that has not fully recognized and respected the customary law system. This article aims to examine the importance of strengthening the role of indigenous peoples through the integration of indigenous law into the national legal system in the context of sustainable natural resource management. Using normative juridical methods and legislative approaches, this article concludes that the legal recognition of indigenous peoples as stated in Article 18B paragraph (2) of the 1945 Constitution, Law No. 32 of 2009 concerning Environmental Protection and Management, and the Constitutional Court Decision No. 35/PUU-X/2012 is an important stepping point in revitalizing the position of indigenous peoples as active legal subjects in sustainable development. An inclusive policy reformulation and participatory mechanisms are needed so that natural resource management is not only oriented towards economic exploitation, but also ensures ecological sustainability and social justice.